If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -3x = 3(4 + -2x) 5 + -3x = (4 * 3 + -2x * 3) 5 + -3x = (12 + -6x) Solving 5 + -3x = 12 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 5 + -3x + 6x = 12 + -6x + 6x Combine like terms: -3x + 6x = 3x 5 + 3x = 12 + -6x + 6x Combine like terms: -6x + 6x = 0 5 + 3x = 12 + 0 5 + 3x = 12 Add '-5' to each side of the equation. 5 + -5 + 3x = 12 + -5 Combine like terms: 5 + -5 = 0 0 + 3x = 12 + -5 3x = 12 + -5 Combine like terms: 12 + -5 = 7 3x = 7 Divide each side by '3'. x = 2.333333333 Simplifying x = 2.333333333
| -5=-4(x-1) | | 8s=21 | | -2(x+4)=5 | | 2=-2+24 | | 7(4+x)=20 | | 6+8x=-7+x | | 5=-2x-27 | | f(x)=2x^2-12x+15 | | 28-5x=13-10x | | x/2-x/5=9/10 | | 15-(9+10b)+(20b-4)=22 | | 5q=4+3p | | p^2+8p-5=0 | | y=37320-50x | | 3x^2-5x+k=0 | | 1/x-1/y=11 | | 24=60-4Q | | 11-3n=19 | | 2x-2=4222 | | 2x-2=422 | | 2x-2=42 | | 4x-18=5x+2 | | (x-2)+2(2x+5)=3(2x+5) | | 1x*1x-3x=0 | | a*x+b*y=c*z | | 5x-5*(2/15)*-4 | | p=15-5q/4 | | 6y=5z+14 | | cos(x)(2*cos(x)+1)=0 | | 5*5*5*5*5*5*5*5*5*5*5*5*5*5*5*5=x | | 12x-8=3x+1 | | x-3y+2z=5 |